Bendix MA-3 Gas Chromatograph system with female model - Bendix Corporation (1971)
Series of photographs depicting the Bendix MA-3 Gas Chromatograph system with a female model. Component parts visible in the photographs include a total output monitor, predynode gate generator, MA-1 Vacuum System, and Time-of-Flight Mass Analyzer.
Keywords: Scientific apparatus and instruments; Spectrometer industry; Mass spectrometry; Time-of-flight mass spectrometry; Women in advertising; Gas chromatography; Bendix Corporation; Gas chromatography--Instruments